ENGINEERING: SOME ASPECTS OF KEY PERSONNEL FURTHER TRAINING - Nepomnyashchyy O.M. (Pressing Problems of Public Administration, 2017)
The article analyzes the forms and methods of engineers-consultants in the construction industrytraining, identifies the main forms of training of such employees in the context of their continuingeducation and substantiates the principles of a highly-quali ed audience training.